2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.106-358
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Heart:Rate Signal Provided by the Zephyr BioHarness 3.0

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The Zephyr Bioharness sensor used in our experiments provides an internal algorithm that calculates HRV based on ECG data. However, in their validation research, Nepi et al concluded that the HRV data provided by this sensor is not reliable [ 36 ]. This, and the fact that the calculations take place only after the initial five minutes of measured HR, were the reasons that we decided not to use HRV data as an input for our models.…”
Section: Psychophysiological Measuresmentioning
confidence: 99%
“…The Zephyr Bioharness sensor used in our experiments provides an internal algorithm that calculates HRV based on ECG data. However, in their validation research, Nepi et al concluded that the HRV data provided by this sensor is not reliable [ 36 ]. This, and the fact that the calculations take place only after the initial five minutes of measured HR, were the reasons that we decided not to use HRV data as an input for our models.…”
Section: Psychophysiological Measuresmentioning
confidence: 99%
“…In recent years wearable devices have attracted significant attention in the scientific community for the evaluation of heart rhythm over extended periods of time in out-of-laboratory settings due to their characteristics of non-invasiveness, flexibility, and compatibility with the skin 8 , 9 . Innovations in wearable technologies have made it possible to record both the electric impulses 10 , 11 (i.e., electrocardiography) and the precordial movements of the heart. Among various techniques, ballistocardiography-BCG (i.e., a measurement of the ballistic forces generated by the ejection of blood into the vessels) and seismocardiography-SCG 12 (i.e., a recording of the chest wall vibrations in response to the atrioventricular contractions) are gaining broad interest for a non-invasive detection of the heart activity in everyday settings 13 , where traditional methods show their main limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Demographic data were collected by survey. Cardiorespiratory signals were recorded through the chest strap BioHarness 3.0 by Zephyr (www.zephyranywhere.com), a reliable wearable device [[1], [2], [3], [4], [5], [6]] that directly records the ECG (mV; raw data) and automatically computes the HR series (bpm; processed data) and the BR series (cpm; processed data).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%